2018
DOI: 10.1016/j.jbiomech.2017.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Thigh-calf contact parameters for six high knee flexion postures: Onset, maximum angle, total force, contact area, and center of force

Abstract: In high knee flexion, contact between the posterior thigh and calf is expected to decrease forces on tibiofemoral contact surfaces, therefore, thigh-calf contact needs to be thoroughly characterized to model its effect. This study measured knee angles and intersegmental contact parameters in fifty-eight young healthy participants for six common high flexion postures using motion tracking and a pressure sensor attached to the right thigh. Additionally, we introduced and assessed the reliability of a method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…12,13 Deep flexion occurs at the limit of motion, and soft-tissue factors are known to influence deep knee flexion kinematics. 14,15 However, the articular shape is still thought to be important in achieving maximal deep flexion. Indeed, total knee replacement design is predicated on restoring normal shape in order to achieve optimal kinematics.…”
mentioning
confidence: 99%
“…12,13 Deep flexion occurs at the limit of motion, and soft-tissue factors are known to influence deep knee flexion kinematics. 14,15 However, the articular shape is still thought to be important in achieving maximal deep flexion. Indeed, total knee replacement design is predicated on restoring normal shape in order to achieve optimal kinematics.…”
mentioning
confidence: 99%
“…This disagreement with previous outcomes is a likely result of our intersegmental force and contact area magnitudes being lower than previous reports 15,19 as our sensor was of higher resolution. 1 Tibial contact force estimates including intersegmental contact from this model appear to be more biologically feasible than prior 2D reports. Our peak tibial compression and shear estimates are almost half 4,12 or 1 to 3 BW 12,79,80 lower than sagitttal plane high knee flexion models that did not account for intersegmental contact.…”
Section: Discussionmentioning
confidence: 86%
“…17 However, their report of thigh-calf contact onset at ∼90°of knee flexion and peak magnitudes of ∼300 N occurring at 120°1 8 contradict prior work. 1,15,19 Similarly, it should be noted that in the work of Wu et al, a 57% reduction in tibiofemoral forces at ∼120°flexion was unexpected as Kingston and Acker, and Zelle et al reported <20 N of thigh-calf contact force at this angle (∼120°) and peak flexion angles of ∼150°i n a similar movement.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…1,2 Thigh-calf forces 3 were applied to a two-dimensional rigid body model and to a finite element model of the tibia, patella, and quadriceps tendon resulting in a compressive force of 3.07 BW versus 4.37 BW when thigh-calf contact was included. 1 Based on our measurements of thigh-calf contact forces and center of force (CoF) in full flexion, 4 on average, peak external extension moments of ≈0.25 Nm/kg about the knee joint result from intersegmental contact. These moments would presumably reduce quadriceps force, a main contributor to both the extension moment and compressive force at the knee joint.…”
Section: Introductionmentioning
confidence: 99%